Effects of nurse‐led supportive‐expressive group intervention for post‐traumatic growth among breast cancer survivors: A randomized clinical trial. Issue 4 (13th December 2021) - Wang, Guorong; Li, Zhuyue; Luo, Xi; Wei, Ru; Liu, Hui; Yang, Jing; Lyu, Jianxia; Jiang, Xiaolian
Abstract: Background: Post‐traumatic growth induced from cancer diagnosis and treatment could benefit the prognosis of cancer survivors, but intervention based on self‐disclosure in group is limited. Objective: Aimed to examine the effectiveness of a supportive‐expressive group intervention on post‐traumatic growth. The impact of the intervention on anxiety and depression were also explored. Design: This randomized clinical trial enrolled patients from June 2017 to September 2018 with a one‐month follow‐up. Data collectors were blinded to patient grouping. Setting: A single center study in Chengdu, China. Participants: One hundred sixty‐eight participants who met the eligibility criteria were randomly assigned to the intervention group ( n = 84) or control group ( n = 84); 46 were excluded and 122 patients finished the one‐month follow‐up. Methods: Participants in the intervention group received nurse‐led support intervention focusing on topics such as "Being a Patient", "Interpersonal Relationships", "Journey for Recovery", and "Planning the Future" while participants in the control group received health education, rehabilitation training etc. according to the nursing routine of breast cancer patients. The intervention was designed in accordance with the diagnosis and treatment process as well as patient needs. Participants in both groups were evaluated three times (T1‐baseline before the intervention, T2‐end of the intervention, and T3‐1 month follow up). Post‐traumatic growth, anxiety and depression were evaluated. Results: Participants in the intervention group reported higher level of post‐traumatic growth ( p < 0.01 or 0.05) and reduced anxiety and depression ( p < 0.01 or 0.05 and p < 0.01 or 0.05). The multilevel model indicated that the intervention significantly promoted post‐traumatic growth ( β T3 = 7.87, p < 0.05) and dimensions of relating to others ( β T3 = 4.26, p < 0.001), personal strength ( β T3 = 4.27, p < 0.01), appreciation of life ( β T3 = 8.69, p < 0.001), and new possibilities ( β T3 = 1.91, p < 0.05), anxiety ( β T3 = −3.63, p < 0.001), and depression ( β T3 = −2.27, p < 0.001), but had no effect on the dimension of spiritual change. In addition, the multi‐level model showed that patients with younger ages ( β = −0.05 −0.52, p < 0.05–0.001), with high school and above education levels ( β = 1.53 9.29, p < 0.01) and accompanied by husbands( β = −1.48 −8.51, p < 0.05) had more effective intervention and patients with religious belief had a better spiritual change level ( β = 1.86, p < 0.001). Conclusions: These findings provide evidence for the potential effectiveness of the nurse‐led intervention on positive benefits of post‐traumatic growth and relieved anxiety and depression for Chinese breast cancer survivors and will inform the design and development of a large randomized controlled trial. Clinical relevance: The supportive‐expression group intervention can be applied independently by nurses. The four themes of self‐disclosure can help patients grow after trauma, and this method can be used as a psychological support technique for breast cancer patients during hospitalization.